2016
DOI: 10.1016/j.msec.2016.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure on anomalous strain-rate-dependent behaviour of bacterial cellulose hydrogel

Abstract: This study is focused on anomalous strain-rate-dependent behaviour of bacterial cellulose (BC) hydrogel that can be strain-rate insensitive, hardening, softening, or strain-rate insensitive in various ranges of strain rate. BC hydrogel consists of randomly distributed nanofibres and a large content of free water; thanks to its ideal biocompatibility, it is suitable for biomedical applications. Motivated by its potential applications in complex loading conditions of body environment, its time-dependent behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…According to our previous research [22,23], there is a high likelihood that the mechanical properties of PHEMA-based nanocomposites are viscoelastic or hyperelastic. For a typical viscoelastic material, the phase difference between the stress input and the strain response leads to a hysteresis, known as dissipated energy [24][25][26]. Thus, the stress-strain relationship of the material is sensitive to the loading speed or strain rate [27,28].…”
Section: Uniaxial Quasi-static Stretchingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous research [22,23], there is a high likelihood that the mechanical properties of PHEMA-based nanocomposites are viscoelastic or hyperelastic. For a typical viscoelastic material, the phase difference between the stress input and the strain response leads to a hysteresis, known as dissipated energy [24][25][26]. Thus, the stress-strain relationship of the material is sensitive to the loading speed or strain rate [27,28].…”
Section: Uniaxial Quasi-static Stretchingmentioning
confidence: 99%
“…The size of the loop represents the energy dissipated during the cyclic deformation. The degree of viscoelasticity (η) is defined as the ratio of the unloading area (the area under the unloading path) to the loading area (the area under the loading path) [24]. Thus, the more energy dissipated during the cyclic loading, the larger hysteretic loop can be obtained; consequently, the ratio η is farther from the value 1, indicating a larger degree of viscoelasticity.…”
Section: Dynamic Cyclic Loadingmentioning
confidence: 99%
“…Thus, it may be concluded that while modelling wet or in-vivo collagen specimens, the parameters obtained with the Ogden model should closely reproduced the deformational behaviour of collagen. The collagen films subjected to hydration or in-aqua conditions (submersion) exhibited a similar response to that observed for bacterial cellulose hydrogel (Gao et al, 2016). ε 1 , ε 2 , ε 3 and ε UTS denote the strain magnitude at the end of Stage I, II, III and IV (ultimate tensile strain), respectively.…”
Section: Effect Of Environmental Conditionsmentioning
confidence: 59%
“…11b). The same approach was used to predict the value of m in biomaterials (Gao et al, 2016;Zhao et al, 2017).…”
Section: Strain-rate Sensitivity Exponentmentioning
confidence: 99%
“…Motion of water during a process of deformation is involved in the network's response, affecting the measurements of its stiffness [43]. In this study, an initial unloading tangent modulus was used as effective elastic property of bulk specimens based on inelastic behaviour from our previous research [12].…”
Section: Measurement Of Effective Elastic Modulusmentioning
confidence: 99%